The Role of Public Schools Principals Inside the Green Line in Teachers' Empowerment and its Relationship with Some Demographic Variables From Teachers' Point of View - Abu Tu'mah, Nadia; Ashour, Mohammed (Jordan Journal of Educational Sciences, 2016)
The study aimed at examining the role played by public schools principals inside the Green Line in teachers' empowerment and its relationship with some demographic variables Teachers' point of View. The sample of the study consisted of (489) subjects, of whom (134) were male and (364) female selected using simple random sampling procedures from public schools inside the Green Line. For data collection, Short and Rinehart (1992) Scale translated and adapted to the Arab environment by Al Mahdi (2007) was used after both validity and reliability for the scale were established. The results of the study showed that the role played by public schools principals inside the Green Line in teachers' empowerment was high. There were statistically significant differences due to gender, in favor of male teachers, in the role played by public schools principals inside the Green Line in the total construct of teachers' empowerment and in teachers' participation in school decision making, teacher's influence, and teaching self- efficacy, due to qualification, in favor of graduate studies teachers, in teachers' participation in school decision making, position and influence, due to school level, in favor of primary schools teachers, in teachers' participation in school decision making and professional development. There were no significant differences due to teaching experience. The study recommended to the importance of maintaining a high level of empowerment of teachers by offering seminars and lectures for school administrators about the teacher training courses enabled